Epstein - Barr virus positive Mucocutaenous ulcer presenting as medication related osteonecrosis of the jaw - A. Yassin Alsabbagh; N. Higgs; K. Moutasim; V. Foria; R. Webb (Elsevier, 2021)
Epstein - Barr virus positive Mucocutaenous ulcer (EBVMCU) is a relatively new entity of the lymphoproliferative disorders, recognised by the WHO in 2017. The usual presentation is of a self-limiting ulcer which can affect the oropharynx, gastrointestinal tract and cutaneous skin.We present an unusual diagnosis of (EBVMCU). The patient had two separate presentations of the same disease: the first followed the expected pathogenesis of EBVMCU with full recovery; the second highlights a complication of the disease resulting in maxillary osteonecrosis.